2020
DOI: 10.24925/turjaf.v8i9.1994-1999.3614
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Flower, Pod and Seed Characteristics Related to Yield Components in Forage Pea Genotypes

Abstract: In this study which was carried out during the 2015 summer season in Eskişehir, the flower, pod and seed characters attributed to yield components were investigated in 12 forage pea genotypes. They showed significant differences in terms of agronomic and morphological (flower, pod, and seed) traits. The highest fresh hay yield with 2171 kg/da and plant height with 106.6 cm were obtained from Populasyon-1. Crackerjack had lower values in some flower traits such as, whereas the higher values of pod and seed trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 8 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…It has been determined in many studies that there is a difference in shoot age weights between cultivars. Okcu et al 2005 used the same cultivars used in our study, Avci et al 2020, the mean fresh shoot weights were between 199 to 243 mg/plant, and Küçüközcü and Avci 2020, in their research including similar cultivars, determined the mean fresh shoot weight as 132.06-161.16 mg/plant. Dumanoglu et al 2021 In the light of the data obtained in their research, reported that species and cultivars with high shoot weight are an important criterion in the evaluation of forage plants used in animal nutrition, and it is important in terms of providing a good genotype preference to scientists, especially in breeding studies.…”
Section: Resultsmentioning
confidence: 62%
See 3 more Smart Citations
“…It has been determined in many studies that there is a difference in shoot age weights between cultivars. Okcu et al 2005 used the same cultivars used in our study, Avci et al 2020, the mean fresh shoot weights were between 199 to 243 mg/plant, and Küçüközcü and Avci 2020, in their research including similar cultivars, determined the mean fresh shoot weight as 132.06-161.16 mg/plant. Dumanoglu et al 2021 In the light of the data obtained in their research, reported that species and cultivars with high shoot weight are an important criterion in the evaluation of forage plants used in animal nutrition, and it is important in terms of providing a good genotype preference to scientists, especially in breeding studies.…”
Section: Resultsmentioning
confidence: 62%
“…While the germination rate of the Töre cultivar was the lowest at 93.33%, the seeds of the other two cultivars were all germinated and a germination rate of 100% was obtained. İt has been reported in many studies that the mean germination rate of forage pea seeds is ≥95% (Okcu et al 2005;Kücüközcü & Avci, 2020;Avci et al 2020;Dumanoglu et al 2021). The vigor index value, which is another examined parameter, was realized as 16.82 on mean, and the lowest vigor index value was obtained from the Töre cultivar, while the highest was obtained from the Özkaynak cultivar.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations